1988
DOI: 10.1183/09031936.93.01010051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of central venous, oesophageal and mouth occlusion pressure with water-filled catheters for estimating pleural pressure changes in healthy adults

Abstract: The validity of the central venous and water-filled oesophageal catheter technique as a measure of pleural pressure changes was tested in ten healthy subjects in different body positions during inspiratory efforts with occluded airways, by comparing the simultaneous changes in mouth pressure (delta Pm) taken to represent pleural pressure changes, in central venous pressure (delta Pcv) and in oesophageal pressure (delta Poes). delta Pcv/delta Pm values were close to unity in the sitting and left lateral positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Almost all mechanically ventilated patients have a central venous access and we showed that the presence of a correctly placed CVC allowed, together with the presented algorithm of processed CVP, to obtain an estimation of respiratory swings of Ppl and P L without further devices. The idea of using the superior vena cava as an alternative site to the esophagus to record pleural pressure goes back to the 70's: con icting results emerged about the correlation between respiratory changes in CVP and P ES , and CVP was found to perform better [9], worse [29] or as good as P ES [30] in providing reliable measure of Ppl. Since different catheter-manometer systems were employed and CVP signal was not always processed, we cannot ultimately speculate about these past results.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all mechanically ventilated patients have a central venous access and we showed that the presence of a correctly placed CVC allowed, together with the presented algorithm of processed CVP, to obtain an estimation of respiratory swings of Ppl and P L without further devices. The idea of using the superior vena cava as an alternative site to the esophagus to record pleural pressure goes back to the 70's: con icting results emerged about the correlation between respiratory changes in CVP and P ES , and CVP was found to perform better [9], worse [29] or as good as P ES [30] in providing reliable measure of Ppl. Since different catheter-manometer systems were employed and CVP signal was not always processed, we cannot ultimately speculate about these past results.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of CVP swings and their correlation with Ppl variations during tidal ventilation were also investigated in spontaneously breathing patients. Flemale et al [ 35 ] compared ΔCVP, ΔPes and mouth occlusion pressure respiratory changes (ΔPm) as an estimate of ΔPpl in 10 healthy adults in different body positions during inspiratory efforts against occluded airways. In that study, ΔPm during the occlusion test was considered representative of ΔPpl according to previous findings [ 46 , 47 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…First, two different systems are compared: one filled with fluid (central venous catheter) and one filled with air (esophageal balloon). Only one of the quoted studies [ 35 ] analyzed ΔCVP and ΔPes with the same fluid-filled system and showed that the central venous catheter as compared to a fluid-filled esophageal catheter provides a valid assessment of ΔPpl in healthy adults during spontaneous breathing. Nevertheless, in the more recent studies where ΔCVP and ΔPes were measured with different systems, a correlation was consistently found between these two parameters.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…UARS leads to sleep fragmentation and negative daytime repercussions (excessive sleepiness, tiredness and fatigue). The characteristic phenomenon of this condition is the awakening associated with RERA, measured by PSG coupled to an esophageal manometry sensor, or with a nasal pressure transducer cannula [220][221][222] .…”
Section: Upper Airway Resistance Syndromementioning
confidence: 99%